Online Gambling Content Supervision Strategy by the Sukabumi City Communication and Information Office - Reza Rifqi Fauzan; Dine Meigawati; Dian Purwanti (Department of Government Studies, Faculty of Social and Political Sciences, Universitas Syiah Kuala, 2026)
The development of information technology has provided various benefits to society; however, it has also led to the emergence of digital deviations, one of which is the widespread dissemination of online gambling content. This phenomenon poses a serious challenge for governments, including local governments, in their efforts to create a safe and healthy digital environment for the public. This study aims to analyze the strategies employed by the Department of Communication and Informatics of Sukabumi City in supervising online gambling content and to identify the obstacles encountered in its implementation. This research adopts a qualitative approach using a descriptive method. Data were collected through observation, in-depth interviews, and documentation, and were analyzed using an interactive analysis model consisting of data reduction, data presentation, and conclusion drawing. The findings reveal that the Department of Communication and Informatics of Sukabumi City has carried out supervision through digital space monitoring, identification of gambling-related content, reporting to the central government, and digital literacy education for the community as a preventive measure. However, several challenges remain, including limited authority of local governments to directly block online gambling content, inadequate human resources, and the rapid evolution of content distribution patterns across digital platforms. The study concludes that the effectiveness of online gambling content supervision requires strengthened institutional capacity, enhanced human resource competencies, and cross-sectoral coordination to ensure optimal, adaptive, and sustainable oversight.